Differentiated instructions with literary works to enhance students’ engagement and reading comprehension - Octaviyanti, Cindy Kurnia; Wahyuni, Sri; Widhiyanto, Widhiyanto (Universitas Islam Sultan Agung, 2025)
This study observes the implementation of differentiated instructions (DI) with literary works to enhance students' engagement and reading comprehension in eighth-grade EFL classroom settings. The investigation employed an exploratory sequential mixed-method design with quantitative data collection through pre-tests and post-tests to assess students' reading comprehension, and a questionnaire was used to measure engagement. Qualitative data were obtained through semi-structured interviews with the teacher to gain insights into DI with literary works implementation. The findings showed significant enhancement in students' engagement and reading comprehension after implementing DI with literary works. The questionnaire results indicated high levels of engagement, with mean scores of 3.32 for behavioral engagement, 3.34 for emotional engagement, and 3.10 for cognitive engagement, suggesting that students were actively involved in the learning process at multiple levels. Furthermore, the pre-test and post-test results showed a notable increase in reading comprehension, with the mean pre-test score at 66.17 and the mean post-test score at 77.46, reflecting an 11.29-point improvement. Moreover, the teacher's reflection highlighted its effectiveness in fostering a student-centered classroom, though the approach required considerable preparation and effort. This study implies that teachers need additional support and training to effectively design and implement DI in their classrooms. Furthermore, this research contributes to the integration of literary works as a medium for differentiated learning, so it provides a novel approach to enhance students' engagement and reading comprehension.